2019
DOI: 10.1111/btp.12693
|View full text |Cite
|
Sign up to set email alerts
|

Trophic niche changes associated with habitat fragmentation in a Neotropical bat species

Abstract: Habitat fragmentation could alter ecological traits including species trophic habits.Here, we used carbon and nitrogen stable isotope ratios to establish differences in isotopic niche width and food resource use between forest fragments and the continuous forest for the phyllostomid frugivorous bat Artibeus lituratus. Using mist nests, we captured bats from two forest fragments and two sites in continuous forest, and sampled from each individual captured three body tissues with contrasting turnover rates (skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…Stevens (2022b), in his study for the Atlantic Forest, warns that food seasonality together with habitat modification is the main driver of reduced specialisation and increased overlap of bat diets. We also expected higher values of niche breadth during the dry season, and our results show a niche expansion (see Figure 2), and this is in line with the optimal foraging theory, where individuals should specialise when resources are plentiful, but when faced with scarcity they tend to increase the number of items included in the diet (Muñoz-Lazo et al 2019; Stephens & Krebs, 1986).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Stevens (2022b), in his study for the Atlantic Forest, warns that food seasonality together with habitat modification is the main driver of reduced specialisation and increased overlap of bat diets. We also expected higher values of niche breadth during the dry season, and our results show a niche expansion (see Figure 2), and this is in line with the optimal foraging theory, where individuals should specialise when resources are plentiful, but when faced with scarcity they tend to increase the number of items included in the diet (Muñoz-Lazo et al 2019; Stephens & Krebs, 1986).…”
Section: Discussionsupporting
confidence: 89%
“…Finally, we shall state that, however, faecal analysis is a widely employed technique; it may have disadvantages when compared with DNA metabarcoding and isotopic composition investigation (Oliveira et al . 2022; Munoz-Lazo et al 2019). These techniques show food items taken for long periods and not just those ingested during a unique consumption event (Schlautmann et al 2021, Vizentin-Bugoni et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These suggest that, in denser fragments A. lituratus have a larger insect component in their diet than in more open forests, irrespective of fragment size or distance between fragments. A similar study examining differences in diet of A. lituratus found in fragments and in contiguous forest found an increase of insect consumption in fragments and in seasons when fruit resources were limited (Muñoz-Lazo et al 2019). Notably, in contrast to our study, Muñoz-Lazo et al (2019) found that this increased the niche breadth of A. lituratus, while we found no significant differences in niche breadth between different sampling 2019) did not characterize the locations they sampled beyond "fragment" and "continuous" forest, we found no significant effect of landscape metrics that are typically characterized as habitat fragmentation (i.e., AREA + ISOLATION, AREA, or PROX1000).…”
Section: Discussionmentioning
confidence: 72%